Le conseguenze psicopatologiche della pedofilia. Un caso clinico - Colosimo, Emilia; Sneider, Maria (Il sogno della farfalla, 2017)
The article deals with paedophilia and provides a historical, cultural and philosophical analysis which dwells in particular on the difference between the concept of pulsion and that of instinct within several different theoretical approaches. The authors also describe the clinical history of a female patient who experienced sexual abuse as a child, outlining details about her psychotherapeutic journey, pathological symptoms and transference and countertransference dynamics. The thesis which is being put forth by the authors is that paedophilia stems from children being thought of as originally perverted human beings, which is something a few psychological theories also support. In order to face paedophilia and cure its pathological outcomes it is therefore necessary to make reference to a new definition of the Self which, according to Human Birth Theory by Massimo Fagioli, constitutes an originally healthy identity.